Spatio-temporal and ontogenetic changes in the diet of the Argentine hake Merluccius hubbsi - Belleggia, Mauro (2014)
The diet and the trophic level of the Argentine hake Merluccius hubbsi was investigated in the south-west Atlantic Ocean. Stomachs from 3405 specimens, ranging from 10 to 94 cm total length, collected on three research cruises carried out during winter 2011 and summer 2012, were examined at the laboratory. Dietary shifts related to sex, maturity stage, size, age, season, region and hour were examined using generalized linear models. The Argentine hake M. hubbsi fed mainly on zooplankton crustaceans (Themisto gaudichaudii, Euphausia lucens and Munida spp.), followed by fish and cephalopods. During summer, cephalopods (mainly Illex argentinus) were the main prey of M. hubbsi, indicating spatio-temporal changes in the diet. This work also revealed ontogenetic dietary changes associated with size, from zooplankton crustaceans during early life stages (E. lucens, T. gaudichaudii and Munida spp.) to fish and cephalopods. The trophic level of M. hubbsi ranged from 3.43 to 4.51 according to season and region. Cannibalism increased with predator length and contributed a maximum of 8.14% to the diet of M. hubbsi during winter on the inner Patagonian continental shelf.